Influence of Main Ocular Variables in #TheDress Perception: An Ophthalmic Survey. (April 2021) - González-Martín-Moro, Julio; Contreras, Inés; Fuentes-Vega, Irene; Prieto-Garrido, Francisco; Castro-Rebollo, María; González-Manrique, Mar; Gómez-Sanz, Fernando; Zamora, Javier
The objective of this study is to study the influence of ocular variables in the perception of #thedress and to develop a logistic regression model that could help predict it. This is a cross-sectional study on 1, 100 subjects. People who did not report one of the two main perceptions were excluded from the study. Dress perception was codified as 0 (white&gold) or 1 (black&blue). The association between dress perception and demographic and main ocular variables (age, gender, binocular visual acuity, grade of nuclear cataract, crystalline lens status [phakic/pseudophakic], spherical equivalent, and ocular health status) was tested using logistic regression. Receiver operation curves were used to test the predictive value of the model. Several variables were found to be related with dress perception. The best model included three variables—Age: adjusted odds ratio (OR) = 1.02 (1.01–1.03), p = 0.08; ocular refraction: adjusted OR = 1.07 (1.02–1.12), p = 0.009; and nuclear cataract grade: adjusted OR = 1.45 (1.05–1.99), p = 0.026. The predictive value of the model was low (area under the curve = 0.62). Older age, nuclear cataract grade, and hyperopia were associated with black&blue perception. The predictive capacity of the developed model was poor. Only a small proportion of the variability in the #thedress perception can be explained by ocular examination.